Role of Natural Killer Cells in HIV-Associated Malignancies - Leal, Fabio E.; Premeaux, Thomas A.; Abdel-Mohsen, Mohamed; Ndhlovu, Lishomwa C. (Frontiers in Immunology, 2017)
Now in its 4th decade, the burden of HIV disease still persists despite significant milestone achievements in HIV prevention, diagnosis, treatment, care, and support. Even with long-term use of currently available antiretroviral therapies (ART), eradication of HIV remains elusive and now poses a unique set of challenges for the HIV infected individual. The occurrence of HIV-associated non-AIDS related co-morbidities outside the scope of AIDS defining illnesses, in particular Non-AIDS defining cancers (NADC), are much greater than the age matched uninfected population. The underlying mechanism is now recognized to be in part related to the immune dysregulated and inflammatory status characteristic of HIV infection that persist despite ART. Natural Killer (NK) cells are multifunctional effector immune cells that play a critical role in shaping the innate immune responses to viral infections and cancer. NK cells can modulate the adaptive immune response via their role in dendritic cell (DC) maturation, removal of immature tolerogenic DCs, and their ability to produce immunoregulatory cytokines. NK cells are therefore poised as attractive therapeutic targets that can be harnessed to control or clear both HIV and HIV-associated malignancies. To date, features of the tumor microenvironment and the evolution of NK-cell function among individuals with HIV-related malignancies remain unclear and may be distinct from malignancies observed in uninfected persons. This review intends to uncouple anti-HIV and anti-tumor NK-cell features that can be manipulated to halt the evolution of HIV disease and HIV-associated malignancies and serve as potential preventative and curative immunotherapeutic options.